Effectiveness, safety and pharmacokinetics of Polo-like kinase 1 inhibitors in tumor therapy: A systematic review and meta-analysis - Wei, Xiao; Song, Mingzhu; Huang, Chan; Yu, Qiao; Jiang, Guirong; Jin, Guanghao; Jia, Xibiao; Shi, Zheng (Frontiers in Oncology, 2023)
Objective To provide a systematic review of existing meta-analysis on the efficacy, safety and pharmacokinetics of the novel Polo-like kinase-1 (Plk1) inhibitors in various tumor treatments, and assess the methodological quality and the strength of evidence of the included meta-analysis. Methods The Medline, PubMed, Embase, etc. were searched and updated on 30 June 2022. 22 eligible clinical trials involving a total of 1256 patients were included for analyses. Randomised controlled trials (RCTs) compared the efficacy or safety, or both of any Plk1 inhibitors with placebo (active or inert) in participants. To be included, studies had to be RCTs, quasi-RCTs, and nonrandomized comparative studies. Results A meta-analysis of two trials reported progression-free survival (PFS) of the overall population (effect size (ES), 1.01; 95% confidence intervals (CIs), 0.73-1.30, I2 =0.0%, P<0.001) and overall survival (OS) of the overall population (ES, 0.91; 95% CIs, 0.31-1.50, I2 =77.6%, P=0.003). 18 adverse events (AEs) reflected that the possibility of occurrence of AEs in the Plk1 inhibitors group was 1.28 times higher than in the control group (odds ratios (ORs), 1.28; 95% CIs,1.02-1.61). The results of meta-analysis showed that the incidence of AEs in the nervous system was the highest (ES, 0.202; 95% CIs, 0.161-0.244), followed by blood system (ES, 0.190; 95% CIs, 0.178-0.201) and digestive system (ES, 0.181; 95% CIs, 0.150-0.213). Rigosertib (ON 01910.Na) was associated with a decreased risk of AEs in digestive system (ES, 0.103; 95% CIs, 0.059-0.147), but BI 2536 and Volasertib (BI 6727) increased risk of AEs in blood system (ES, 0.399; 95% CIs, 0.294-0.504). Five eligible studies reported the pharmacokinetic parameters of the low dosage (100 mg) cohort and the high dosage (200 mg) cohort, and there was no statistical difference in the total plasma clearance, terminal half-life and apparent volume of distribution at steady state. Conclusions Plk1 inhibitors work better in improving OS and they are well tolerated, effective and safe in reducing the severity of illness while improving the quality of life, especially in patients with non-specific tumors, respiratory system tumors, musculoskeletal system tumors, and urinary system tumors. However, they fail to prolong the PFS. From the vertical whole level analysis, compared to other systems in the body, Plk1 inhibitors should be avoided as far as possible for the treatment of tumors related to the blood circulatory system, digestive system and nervous system, which were attributed to the intervention of Plk1 inhibitors associated with an increased risk of AEs in these systems. The toxicity caused by immunotherapy should be carefully considered. Conversely, a horizontal comparison of three different types of Plk1 inhibitors suggested that Rigosertib (ON 01910.Na) might be relatively suitable for the treatment of tumors associated with the digestive system, while Volasertib (BI 6727) might be even less suitable for the treatment of tumors associated with the blood circulation system. Additionally, in the dose selection of Plk1 inhibitors, the low dose of 100 mg should be preferred, and meanwhile, it can also ensure the pharmacokinetic efficacy that is indistinguishable from the high dose of 200 mg. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42022343507.